Critical role for Invariant chain in CD1d-mediated selection and maturation of Vα14-invariant NKT cells - Sillé, Fenna C. M. (2011)
The development and maturation of Vα14 invariant (i)NKT cells in mice requires CD1d-mediated lipid antigen presentation in the thymus and the periphery. Cortical thymocytes mediate positive selection, while professional APCs are involved in thymic negative selection and in terminal maturation of iNKT cells in the periphery. CD1d requires entry in the endosomal pathway to allow antigen acquisition for assembly as lipid/CD1d complexes for display to iNKT cells. This process involves tyrosine-based sorting motifs in the CD1d cytoplasmic tail and invariant chain (Ii) that CD1d associates with in the endoplasmic reticulum. The function of Ii in iNKT cell thymic development and peripheral maturation had not been fully understood. Using mice deficient in Ii and the Ii-processing enzyme cathepsin S (catS), we addressed this question. Ii(−/−) mice but not catS(−/−) mice developed significantly fewer iNKT cells in thymus, that were less mature as measured by CD44 and NK1.1 expression. Ii(−/−) mice but not catS(−/−) mice developed fewer Vβ7(+) cells in their iNKT TCR repertoire than WT counterparts, indicative of a change in endogenous glycolipid antigen/CD1d-mediated iNKT cell selection. Finally, using a Mycobacterium tuberculosis infection model in macrophages, we show that iNKT developed in Ii(−/−) but not catS(−/−) mice have defective effector function. Our data support a role for professional APCs expressing Ii, but no role for catS in the thymic development and peripheral terminal maturation of iNKT cells.